LEGAL AND REGULATORY FRAMEWORK FOR MONITORING ONLINE STORES - Derar Al-Daboubi; Jalal Alqhaiwi (UUM Journal of Legal Studies, 2022)
This study has been an attempt to find a legal and regulatory framework to monitor online stores under Jordanian legislation. The need for such a framework has become even more urgent, especially after the COVID-19 pandemic that has adversely affected traditional trade, and contributed to the increase in commercial transactions concluded via the internet. Therefore, it is necessary to understand the essence of the online store and the extent to which owners of such online stores can be subjected to the same obligations of the traditional merchant. This is to enable the relevant authorities to regulate the activities of the online store and these regulations will have to be consistent with the provisions of the country’s legal framework. The present study has also identified the key challenges encountered by online stores when carrying out their activities. In conclusion, the study has proposed some suggestions which were based on existing legislations regulating electronic commercial transactions. These suggestions were aimed at harmonizing the legislations of developing countries with the existing international legal rules regulating online stores.